DETERMINAN YANG BERHUBUNGAN TERHADAP KEPUTUSAN PASIEN MEMANFAATKAN PELAYANAN RAWAT JALAN DI RUMAH SAKIT ANNA KOTA BEKASI TAHUN 2020 - Ayu Mutiara Rani, (2021)
The outpatient services play an important role in the prevention and cure of diseases, but there is a decrease in the use of outpatient service at Anna Hospital, Bekasi City. The coverage of outpatient visits at Anna Hospital in Bekasi City for the last three years, there were 147.578 visits in year 2018, 139.846 visits in year 2019, and it were decreased to 105.322 visits in year 2020. The purpose of this study was to analyze the determinants related to the utilization of outpatient services at Anna Hospitals, Bekasi city. This study used a cross-sectional research design. The sample in this research amounted to 288 patients who were selected with a proportionate stratified random sampling technique based on inclusion and exclusion criteria as well as the type of polyclinic in the hospital. The results of the chi-square test analysis showed that of the three organizational factors, two factors were related to the patient's decision to utilize outpatient services, namely the availability of facilities (p-value=0,000) and patient safety (p-value=0,000). While, all interaction factors between consumers and health workers are related to the utilization of outpatient services, namely education (p-value=0,000), income (p-value-0,000), doctor services (p-value=0,000), nursing service (p-value=0,000), and perception of pain (p-value=0,000). It is recommended for the hospital to maintain and improve its services, especially for polyclinics with the lowest outpatient visits by developing and evaluating periodically, so that they can meet the needs of patients undergoing outpatient treatment.